Building psychological contracts in security-risk environments: evidence from Colombia and Mexico. (2015) - Ramirez, Jacobo; Vélez-Zapata, Claudia; Madero, Sergio
This paper examines the reciprocal obligations between employers and employees that are framed as psychological contracts in security-risk environments. A total of 30 interviews based on psychological contract frameworks, duty-of-care strategies in terms of human resource management (HRM) systems and the impacts of narcoterrorism on firms were conducted with human resources (HR) personnel, line managers and subordinates at eight national and multinational corporations (MNCs) with subsidiaries in Colombia and Mexico. Our findings generally support the existence of a relational psychological contract in our sample. Duty-of-care strategies based on both HRM systems and the sensitivities of HR personnel and line managers to the narcoterrorism context, in combination with both explicit and implicit security policies, tend to be the sources of the content of psychological contracts. We propose a psychological contract model based on HRM systems and security and control policy in a narcoterrorism context for the further study of firms' duty-of-care strategies.